Exploring the Personality of Mbok Wilis in A. Mustafa's Novel - Sari, Ayu Novita; Rujiana, Evita (Cultural Narratives, 2023)
This study aims to describe and uncover the main character's personality in the novel "Anak Gembala yang Tertidur Panjang di Akhir Zaman" by A. Mustafa. This research uses a descriptive qualitative method. Depictions and descriptive qualitative research are in the form of portrayals and certain circumstances with the interactive method. The interactive method helps study the content of documents. The data source in this study is the novel "Anak Gembala Yang Tertidur Panjang di Akhir Zaman" by A. Mustafa. The data collection technique in this research is content analysis. The characterization of the main character of this novel is quite interesting because he is cross-dressing, so a study was conducted using the theory of literary psychology. The main character is Mbok Wilis, a man who acts as a woman daily. The results of this study are that Mbok Wilis has a spirit of enthusiasm, never gives up, cares for others, easily believes, quickly moves, and is complex.